2010
DOI: 10.1177/1753944710387629
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of nebivolol in Hispanics with stage I-II hypertension: a randomized placebo-controlled trial

Abstract: In Hispanics with stage I-II hypertension, 8-week nebivolol monotherapy resulted in significant reductions in blood pressure. The safety and tolerability profile of nebivolol was similar to that of placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Additionally, the nonobese placebo group had a higher percentage of Hispanics than the other nonobese pooled treatment groups. A greater placebo response has been observed in Hispanic participants in phase 3 nebivolol and nebivolol/valsartan clinical trials, thus the placebo response in this study may be overestimated. Despite this aberration, the nebivolol/valsartan SPC was still more effective than placebo in this group .…”
Section: Study Limitationsmentioning
confidence: 60%
“…Additionally, the nonobese placebo group had a higher percentage of Hispanics than the other nonobese pooled treatment groups. A greater placebo response has been observed in Hispanic participants in phase 3 nebivolol and nebivolol/valsartan clinical trials, thus the placebo response in this study may be overestimated. Despite this aberration, the nebivolol/valsartan SPC was still more effective than placebo in this group .…”
Section: Study Limitationsmentioning
confidence: 60%
“…[12] Results from the small number of antihypertensive trials that enrolled significant numbers of Hispanic patients are also limited because ethnicity and/or race were usually self-reported,[40–42] which may have affected the uniformity of data capture, and in most cases no distinctions were made between Hispanic Whites and Hispanic Blacks.…”
Section: Efficacy Of Antihypertensive Agents In Hispanics: Review mentioning
confidence: 99%
“…Analysis of these articles identified 17[30,31,4054] publications involving 15 different studies that specifically reported on the efficacy and safety of antihypertensive agents in Hispanic patients. Additional data from the INVEST study (table I provides full names of trial acronyms used in this article) was also included from a publication not identified in this search.…”
Section: Efficacy Of Antihypertensive Agents In Hispanics: Review mentioning
confidence: 99%
See 2 more Smart Citations